PENGARUH REMINISCENCE THERAPY TERHADAP NYERI PADA LANSIA PENDERITA HIPERTENSI DI PANTI SOSIAL TRESNA WERDHA UNIT BUDI LUHUR, BANTUL YOGYAKARTA - Isnanto (Jurnal Kesehatan, 2020)
Background: Hypertension is a disease with an incidence of around 1.13 billion in the world, and the Special Region of Yogyakarta is ranked second in the incidence of hypertension in Indonesia. The high incidence of hypertension causes other related problems such as Diabetes Mellitus (DM), stroke, and also pain. Pain management in patients with hypertension can be done in a non-pharmacological manner. One of the non-pharmacological therapies that want to know the effect is reminiscence therapy. The purpose of this study was to determine the effect of reminiscence therapy on hypertension sufferers' pain. This research method is a quasi-experimental research with one group of comparative pretest-posttest design. The sample used was 30 elderly people with hypertension who experience pain. Statistical test results with the Wilcoxon test showed a value of Z 4.80, this indicates there is a significant effect. The results of the mean difference in pain scale also there is a decrease in pain scale of 3.8. The conclusion of this study is therapeutic reminiscence influences reducing the scale of pain in elderly patients. Researcher suggests reminiscence therapy could be an option for nursing intervention in patients with a diagnosis of acute pain. Keywords: pain, hypertension, reminiscence therapy.